2023
DOI: 10.1017/s1355617723000115
|View full text |Cite
|
Sign up to set email alerts
|

Greater subjective cognitive decline severity is associated with worse memory performance and lower entorhinal cerebral blood flow in healthy older adults

Abstract: Objective: Subjective cognitive decline (SCD) is a potential early risk marker for Alzheimer’s disease (AD), but its utility may vary across individuals. We investigated the relationship of SCD severity with memory function and cerebral blood flow (CBF) in areas of the middle temporal lobe (MTL) in a cognitively normal and overall healthy sample of older adults. Exploratory analyses examined if the association of SCD severity with memory and MTL CBF was different in those with lower and higher cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 79 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…Reduction in CBF, as one of the early symptoms of AD/ADRD has been observed in numerous human and animal models of the disease [ 1 , 2 , 41 ]. The strong correlation between the severity of brain hypoperfusion and the extent of cognitive deficits [ 3 , 4 ] underscores the importance of studying this phenomenon. Understanding the underlying mechanisms of impaired vascular reactivity and CBF reduction is essential for the development of effective interventions and therapies to prevent or delay cognitive decline in AD/ADRD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction in CBF, as one of the early symptoms of AD/ADRD has been observed in numerous human and animal models of the disease [ 1 , 2 , 41 ]. The strong correlation between the severity of brain hypoperfusion and the extent of cognitive deficits [ 3 , 4 ] underscores the importance of studying this phenomenon. Understanding the underlying mechanisms of impaired vascular reactivity and CBF reduction is essential for the development of effective interventions and therapies to prevent or delay cognitive decline in AD/ADRD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided evidence suggesting that brain hypoperfusion, a condition characterized by a reduction in cerebral blood flow (CBF), can contribute to neurodegeneration, leading to cognitive impairments in individuals with Alzheimer’s Disease (AD) and Alzheimer’s Disease-Related Dementias (ADRD) [ 1 , 2 ]. Human studies have identified a strong correlation between the severity of CBF reduction and the extent of cognitive deficits, highlighting the importance of addressing CBF reduction as one of the early symptoms of AD/ADRD [ 3 , 4 ]. Despite the significant attention on the impact of CBF reduction on cognitive function and brain pathology in AD/ADRD, the genetic, molecular, and cellular mechanisms underlying this relationship remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%